COMPUTATIONAL FLUID DYNAMICS (CFD) INVESTIGATION ON THERMAL PERFOMANCE OF HEAT SINKS IN ELECTRONIC EQUIPMENT - MOHD DAUD, MOHAMMAD SYAHMIE (2018)
Heat sink is a passive heat exchanger which transfer the heat to the fluid domain from the devices especially integrated circuit such as CPU, graphic card, chipset and hard disk drives that produce heat. Basically, to dissipate more heat and increase the rate of heat transfer, the area of heat sink need to be increase as well. The method is already applied in industry such as adding fins to the heat sink. Then, the steady-air flow, rate of heat transfer and fins efficiency can be enhanced. If these three main factor cannot be done, it will result failure in electric equipment. As a result, the most efficient cooling is still remain a challenge in engineering especially this thermal case.